Alternatives to cash prices in fed-cattle price discovery - J. Mintert; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 2000)
Price discovery in fed cattle markets is a significant concern as cash market volume declines and trade becomes more sporadic. Producers need to consider other sources of pricing information when negotiating cash trade and long-term marketing agreements. This study evaluated several alternative price sources for producers to consider. Live cattle futures and wholesale boxed-beef prices offer the most promise; however, both also have limitations associated with their use.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Cattle price discovery; Futures markets; Wholesale beef prices